Information sourcing in an automated Nigerian academic library (2011)
Information seeking is a fundamental human process closely related to learning and problem solving, thus the information sourcing characteristics of users of the Kenneth Dike Library, University of Ibadan is examined with a view to evaluating their use of modern Information and Communication Technology (ICT) facilities provided. Use patterns, user satisfaction with the ICT facilities, and user preference of manual and electronic facilities provided are evaluated. Descriptive survey research to appraise the adequacy of modern ICT in the library was carried out. Questionnaire, interview and participatory observation methods were used. The results show that majority of the users (75%) prefer the new ICT facilities to the manual, even though they encounter difficulties in use. Lack of constant power supply, limited access to online resources, lack of adequate user and staff training and non-creation of awareness for the ICT facilities is identified as some of the problems. Recommendations are made for future improvement and continuous evaluation.